2017
DOI: 10.11648/j.ajns.20170603.20
|View full text |Cite
|
Sign up to set email alerts
|

School Bag Usage, Postural and Behavioral Habits and Its Effect on Back Pain Occurrence Among School Children

Abstract: Abstract:Back pain is currently growing as a major health problem among school age group children, which can limit or hinder their daily life activities. The aim of the study was to determine the effect of school bag use, postural and behaviors habits on back pain occurrence among school children. Descriptive correlation design was used. This study was conducted at ten governmental preparatory schools from both rural and urban schools in Menouf district, Menoufia Governorate, Egypt. Random sample of 598 prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
5
7
0
1
Order By: Relevance
“…This study displays no significant association between location and MSP in agreement with some previous studies on students (AL-Qato et al, 2012;El-Nagar & Mady, 2017;Lewandowski & Lukaszewska, 2014). Under the NYCBE, maintaining the provision of free transport services alongside with the zoning systems may be helping students to avoid MSP.…”
Section: What Are the Factors Causing Msp Among Students?supporting
confidence: 91%
See 1 more Smart Citation
“…This study displays no significant association between location and MSP in agreement with some previous studies on students (AL-Qato et al, 2012;El-Nagar & Mady, 2017;Lewandowski & Lukaszewska, 2014). Under the NYCBE, maintaining the provision of free transport services alongside with the zoning systems may be helping students to avoid MSP.…”
Section: What Are the Factors Causing Msp Among Students?supporting
confidence: 91%
“…Studies report conflicting statistics on whether urban or rural locations can enhance pain intensity (Darmawan et al, 1992;Haq et al, 2005;Mwaka et al, 2014)). Some studies indicate no significant relations between location and MSP (AL-Qato, 2012), location and spinal pain (Lewandowski & Lukaszewska, 2014), location and back pains (BP) (El-Nagar & Mady, 2017).…”
Section: Location and Musculoskeletal Painsmentioning
confidence: 99%
“…Similar results were reported by two other studies that investigated back pain in schoolchildren (24,25). On the other hand, El-Nagar and Mady reported that the majority of students who felt back pain in their study carried the schoolbag on one shoulder or in one hand (6), which is not in agreement with our results. Most of the students from both of our groups (50.6%) reported that they sometimes felt tiredness while carrying the schoolbag (64.1% of fifth-grade students and 37.5% of sixth-grade students), with no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies showed a higher prevalence of back pain in girls compared to boys, while other studies reported that boys are at greater risk to develop back pain or they found no statistically significant gender difference in the prevalence of back pain (3)(4)(5)(6). According to the National Health and Nutrition Examination Survey Series II, non-specific back pain occurs before the age of 20 in approximately 11% of the general population (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation